The Use of Core Warming as a Treatment for Coronavirus Disease 2019 (COVID-19): an Initial Mathematical Model - Mercado-Montoya, Marcela; Bonfanti, Nathaniel; Gundert, Emily; Drewry, Anne Meredith; Bedimo, Roger; Kostov, Victor; Kostov, Konstantin; Shah, Shailee; Kulstad, Erik (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Background: Increasing data suggest that elevated body temperature may be helpful in resolving a variety of diseases, including sepsis, acute respiratory distress syndrome (ARDS), and viral illnesses. SARS-CoV-2, which causes coronavirus disease 2019 (COVID-19), may be more temperature sensitive than other coronaviruses, particularly with respect to the binding affinity of its viral entry via the ACE2 receptor. A mechanical provision of elevated temperature focused in a body region of high viral activity in patients undergoing mechanical ventilation may offer a therapeutic option that avoids arrhythmias seen with some pharmaceutical treatments. We investigated the potential to actively provide core warming to the lungs of patients with a commercially available heat transfer device via mathematical modeling, and examine the influence of blood perfusion on temperature using this approach. Methods: Using the software Comsol Multiphysics, we modeled and simulated heat transfer in the body from an intraesophageal warming device, taking into account the airflow from patient ventilation. The simulation was focused on heat transfer and warming of the lungs and performed on a simplified geometry of an adult human body and airway from the pharynx to the lungs. Results: The simulations were run over a range of values for blood perfusion rate, which was a parameter expected to have high influence in overall heat transfer, since the heat capacity and density remain almost constant. The simulation results show a temperature distribution which agrees with the expected clinical experience, with the skin surface at a lower temperature than the rest of the body due to convective cooling in a typical hospital environment. The highest temperature in this case is the device warming water temperature, and that heat diffuses by conduction to the nearby tissues, including the air flowing in the airways. At the range of blood perfusion investigated, maximum lung temperature ranged from 37.6°C to 38.6°C. Conclusions: The provision of core warming via commercially available technology currently utilized in the intensive care unit, emergency department, and operating room can increase regional temperature of lung tissue and airway passages. This warming may offer an innovative approach to treating infectious diseases from viral illnesses such as COVID-19, while avoiding the arrhythmogenic complications of currently used pharmaceutical treatments.